Oxidation of saturated hydrocarbons to alkyl hydroperoxides by a 'H 2O2/titanosilicalite-1/NaOH/MeCN' system - Shul'pin, Georgiy B.; Kirillova, Marina V.; Sooknoi, Tawan; Pombeiro, Armando J.L. (My University, 2008)
Hydrogen peroxide oxidizes alkanes at room temperature to produce the corresponding alkyl hydroperoxides in the presence of titanosilicalite-1, NaOH and acetonitrile. The reaction proceeds with low regio- and bond-selectivity and its mechanism apparently involves the formation of hydroxyl radicals. © 2008 Springer Science+Business Media, LLC.
Keywords: Alkanes; Alkyl hydroperoxides; Hydrogen peroxide; Nano structures; Oxidation; Titanium catalysts